A Case Report of Ethylene Oxide (EO) Contamination in Ice Cream “Häagen-Dazs”, How in Indonesia? - Elanda Fikri; Yura Witsqa Firmansyah (Fakultas Teknik, 2022)
The availability of a safe food supply for the community is a right that must be fulfilled. One of the food supplies is dairy products such as milk. Milk can be processed into various types of products, including ice cream. On 8 July 2022, the European Union Rapid Alert System for Food and Feed (RASFF) reported a case of Ethylene oxide (EO) contamination in French Häagen-Dazs brand vanilla ice cream with levels exceeding quality standards (maximum of 20 mg/kg). This study aims to disseminate information about chemical contamination of ethylene oxide in ice cream and how the Indonesian authorities respond in to prevent and control the spread of contamination. The Previous case reports on 6 July 2022, authorities in France through RappelConso, and on 7 July 2022, Food Standards Australia New Zealand (FSANZ) published public information regarding the voluntary recall of Häagen-Dazs vanilla flavor ice cream by the manufacturer because it contains EO. Meanwhile, on 8 July 2022, the Singapore Food Agency (SFA) ordered importers to recall the product. In 19 July 2022, The Indonesian government through the Badan Pengawas Obat dan Makanan (BPOM) has withdrawn the vanilla flavored Haagen Dazs ice cream product circulating in Indonesia. The hypothesis that can be formulated on Ethylene oxide contamination in ice cream is the use of pesticides containing EO on vanilla flowers (the raw material for making Häagen-Dazs ice cream with vanilla flavor) leaving a high residue. The Häagen-Dazs ice cream industry must implement a good HACCP system, including a sound and safe selection of raw materials